Kolme tarinaa lasista : suomalainen lasimuotoilu 1946-1957 - Koivisto, Kaisa; Kokkonen, Jyri (Lasitutkimuksia, ISSN 0359-0658, 2001)
Abstract.
Keywords: 1940-luku; 1950-luku; 1946-1957; lasi; lasitaide; taidelasi; lasiesineet; lasiteollisuus; muotoilu; muotoilijat; teollinen muotoilu; taideteollisuus; historia; Suomi